Validation of leaf cover analysis software (LCAS) to monitor lettuce cultivated with organic fertiliser - Marques, Vitor da Costa; Silva, Jaqueline dos Santos; Presumido, Pedro Henrique; Dal Bosco, Tatiane Cristina; Michels, Roger Nabeyama; Bertozzi, Janksyn (Acta Iguazu, 2019)
Composting and vermicomposting are techniques used to stabilise organic waste and produce nutrient-rich fertilisers. Experiments that analyse cultures and different fertilisers applied to soil require a heavy workload and time to monitor plant development. Thus, alternative methods to facilitate this monitoring need to be created. The aim of this paper was to assess the development of lettuce cultivated with eight types of fertilisers derived from composting and vermicomposting, and to compare the traditional data collection method with leaf cover analysis software (“LCAS”). The assessed items were growth, diameter, number of leaves, fresh mass, dry mass, and leaf cover obtained using the software. Overall, the lettuce cultivars that received organic fertiliser developed better than the witness, especially in relation to treatments containing ash, such as the C4 compost (Mud, Ash and Pruning litter) and V2 vermicompost (Mud, Ash and Coffee husk). LCAS proved to be an effective tool to monitor the growth of lettuce cultivars in comparison with the traditional method since statistically the pattern of behaviour of the treatments was similar for plant cover, diameter, length, and fresh and dry masses.